(untitled) (Asian Journal of Plant Biology, 2015)
Glycine wightii species is native to Brazil and Africa. It is often known as an important climbingÂ vine-like perennial soybean. It is in the family of Leguminosae, within the sub-familyÂ Papilionoideae, under the genus Glycine and with the sun-genus Bracteata. In a prior work, weÂ modeled the growth of the bacterium Glycine wightii from published literatures to acquire crucial growth constants. We learned that the modified Gompertz model via nonlinear regression usingÂ the least square method was the most effective model to describe the growth curve. Nevertheless,Â the use of statistical tests to choose the best model relies heavily on the residuals of the curve to be statistically robust. More often than not, the residuals must be tested for conformation toÂ normal distribution. In order for this assumption to be met, we perform statistical diagnosis testsÂ such as the Kolmogorov-Smirnov, Wilks-Shapiro and D’agostino-Pearson tests.